2014
DOI: 10.1016/j.physd.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Stability of stationary solutions for nonintegrable peakon equations

Abstract: The Camassa-Holm equation with linear dispersion was originally derived as an asymptotic equation in shallow water wave theory. Among its many interesting mathematical properties, which include complete integrability, perhaps the most striking is the fact that in the case where linear dispersion is absent it admits weak multi-soliton solutions -"peakons" -with a peaked shape corresponding to a discontinuous first derivative. There is a one-parameter family of generalized Camassa-Holm equations, most of which a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The case of b = 2 is exactly the CH equation, while the case of b = 3 recovers the DP equation. According to various tests for integrability, it is known that the cases of b = 2 and b = 3 are the only integrable equations within this family [32][33][34][35]. However, for any b, all those equations admit peakon solutions [31].…”
Section: Introductionmentioning
confidence: 99%
“…The case of b = 2 is exactly the CH equation, while the case of b = 3 recovers the DP equation. According to various tests for integrability, it is known that the cases of b = 2 and b = 3 are the only integrable equations within this family [32][33][34][35]. However, for any b, all those equations admit peakon solutions [31].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for b 0.85 we noticed that peakons were emitted from the ramp-cliffs, with the former emerging as robust traveling waves. We investigated this byproduct of the numerical scheme by considering the implications of Theorem 3 in [20]. In particular, it can be shown that if m(x, t = 0) > 0, then m(x, t) > 0, ∀t > 0 holds which in fact is the case as per the Gaussian initial data employed in this work.…”
Section: Numerical Timesteppingmentioning
confidence: 94%
“…The behavior observed separately in each of the parameter ranges b > 1 and b < −1 can be understood as particular instances of the soliton resolution conjecture [19], a somewhat loosely defined conjecture which states that for suitable dispersive wave equations, solutions with "generic" initial data will decompose into a finite number of solitary waves plus a radiation part which disperses away. The authors of [20] provide a first step towards explaining this phenomenon analytically in the "lefton" regime b < −1. Indeed, they show that in this parameter range a single lefton solution is orbitally stable, by applying the approach of Grillakis, Shatah and Strauss in [21].…”
Section: Introductionmentioning
confidence: 99%
“…[43]), which says that for any suitable dispersive evolutionary PDE (not necessarily integrable), generic initial data should decompose into a train of solitary waves together with radiation which decays to zero as t → ∞. Apart from intensive studies of the integrable cases b = 2, 3, further analytical and numerical support for the behaviour reported by Holm and Staley has taken a while to materialize: an orbital stability result for a single lefton when b < −1 was proved in [27], while there are various well-posedness and rigidity results (see [29,38] and references); yet linear stability/instability results for peakons, ramp/cliff solutions and leftons across the full range of b values have been found only very recently [7,31].…”
Section: Introductionmentioning
confidence: 97%
“…(See [27] for instance, where a Banach subspace of a weighted Sobolev space was considered in order to prove an orbital stability property of stationary solutions when b < −1. )…”
Section: Introductionmentioning
confidence: 99%